2001
DOI: 10.1902/jop.2001.72.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Predictable Multiple Site Root Coverage Using an Acellular Dermal Matrix Allograft

Abstract: Treatment with ADM was an effective and predictable procedure for root coverage. The orientation of the material did not affect the treatment outcome for any of the parameters tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
134
1
16

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(167 citation statements)
references
References 60 publications
16
134
1
16
Order By: Relevance
“…However, although both show similar results in terms of gingival biotype, the collagen matrix increases the same way as increased connective grafts 23 . Henderson et al 24 found similar increases in gingival biotype. Recall studies indicate thickness of the gum (gingival biotype) is more decisive than the amount of keratinized gingiva to prevent future gum recession 24 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, although both show similar results in terms of gingival biotype, the collagen matrix increases the same way as increased connective grafts 23 . Henderson et al 24 found similar increases in gingival biotype. Recall studies indicate thickness of the gum (gingival biotype) is more decisive than the amount of keratinized gingiva to prevent future gum recession 24 .…”
Section: Discussionmentioning
confidence: 80%
“…Henderson et al 24 found similar increases in gingival biotype. Recall studies indicate thickness of the gum (gingival biotype) is more decisive than the amount of keratinized gingiva to prevent future gum recession 24 . It is important to highlight that an important factor to increase the risk of future gingival recession is a thin gingival biotype 25,26 .…”
Section: Discussionmentioning
confidence: 80%
“…In the present case report, alloderm® has been used underneath the flap to increase the predictability of the procedure. In a study, alloderm® has been used with coronally advanced flap procedure, mean gingival recession decreased from 4.20 to 0.25 mm when basement side of the graft was toward the site and it decreased from 3.70 to 0.15 mm when connective tissue side was toward the site [6]. When double papilla flap combined with GTR was compared with coronally advanced flap combined with GTR, the study had shown that there was significant decrease in recession in both the cases and no significant difference between the groups [10].…”
Section: Dentistry Section Abstractmentioning
confidence: 99%
“…Un aloinjerto de matriz dérmica acelular (AMDA) se ha reportado recientemente en la literatura, mostrando resultados clínicos favorables en el cubrimiento de recesiones gingivales (24)(25)(26)(27).…”
Section: Introductionunclassified